ANALYSIS OF VILLAGE GOVERNANCE IN KEBANGGAN VILLAGESUMBANG DISTRICT, BANYUMAS DISTRICT - Lulu Dwi Setyani; Suryoto Suryoto; Emilius Gudonohadi (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This research is entitled